WAVE CHARACTERISTICS ANALYSIS OF PERAK WATERS SURABAYA - Zainul Hidayah (Jurnal Kelautan, 2009)
This research was intended to understand the wave’s characteristics of the study area. Wave’s parameters that were observed in this research including wave period (T), wave length (L), wave height (H), wave velocity (C) and wave energy (E). Another objective of this study was also to produce a topographic map of the sea floor for the study area. Wave’s data of this study was gain from an electronic sensor called MAWS (Marine Automatic Wave Sensor). This sensor is located in a Naval Base of Surabaya. Result of this study showed that the Perak Port was located in a relatively shallow waters area, with maximum water depth approximately 27 meters. The average of observed wave length and wave period during the study was 2.005 meters and 1.0875 seconds. Moreover, this study was also observed that the average of wave height of the area 0.2375 meters, with wave velocity just about 1.6975 m/s. Key Words : wave period , wave length, wave height, wave velocity, wave energy